ABC bridging tensions between logics of care and business: The perspective of paradox theory - Conceição, A.; Major, M.; Clegg, S. (44th Annual EAA Congress, 2022)
In this paper we present an analysis of how activity-based costing (ABC) was included amongst austerity policy prescriptions within the healthcare sector. Relying on the proposition that an increasing quality of outcomes is achievable simultaneously with a reduction in costs, ABC straddles the contradictory logics of care and business. We draw on case study research and combine elements of institutional logic and paradox theory to analyze how the introduction of ABC as a device for cost accounting can be both integrative and disintegrative. ABC became a device that made better cross-sectional communication between administrators and clinicians possible and was able to mediate antagonistic institutional logics but only when actor’s interests and power were aligned in the hospital in question.